2021
DOI: 10.1097/scs.0000000000007921
|View full text |Cite
|
Sign up to set email alerts
|

Missense Variants Within GJB2 Gene Locus and the Risk of Hearing Defects in Nonsyndromic Cleft Lip and Palate

Abstract: The aim of the study was to investigate the role of variants in GJB2 gene in the etiology of hearing defects in nonsyndromic cleft lip/palate. Method: Saliva samples were obtained from cases (subjects with orofacial clefts) and control (subjects without orofacial clefts) who consented to the study. Deoxyribonucleic acid (DNA) was extracted using standardized protocol at Butali Lab (Iowa, IA). Primers for the coding region of GJB2 was designed using Primer 3 (http:// bioinfo.ut.ee/primer3-0.4.0/) and optimized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…63 Similarly, micro-deletion in 6p25.3 involving DUSP22gene has also been reported. 64 Adeyemo et al 65 reported that variants in the GJB2 gene is implicated in the etiology of hearing defects in non-syndromic cleft lip and palate Other authors have also reported gene mutations in patients with hearing impairment and cleft. 66,67 Otological problems peculiar to patients with orofacial clefts tends to involve the middle and/or inner ear.…”
Section: Discussionmentioning
confidence: 99%
“…63 Similarly, micro-deletion in 6p25.3 involving DUSP22gene has also been reported. 64 Adeyemo et al 65 reported that variants in the GJB2 gene is implicated in the etiology of hearing defects in non-syndromic cleft lip and palate Other authors have also reported gene mutations in patients with hearing impairment and cleft. 66,67 Otological problems peculiar to patients with orofacial clefts tends to involve the middle and/or inner ear.…”
Section: Discussionmentioning
confidence: 99%